Effectiveness of School Leadership and Management Course For Headmasters - Fook, Chan Yuen (2004)
The prime purpose of this study was to examine the effectiveness of the School Leadership and Management Course (KPKS) through three levels namely participants satisfaction, learning enhancement and organizational effectiveness. This study also attempted to investigate the relationships among these three variables. The research methodology employed here was of correlational and descriptive. The survey questionnaires and KPKS tests were used in the collection of data. Purposive sampling of clusters was preferred as this technique seem to be more suitable in studying course participants according to cohorts in a certain year. All the 221 headmaster participants (six groups) attended the KPKS course in the year 2002 were selected as clusters for the study. Besides that, multistage stage cluster sampling was also used. All 221 headmaster participants plus their 221 senior assistants and their 2210 teachers (10 teachers per school) participated in this study. The data was analyzed using means, standard deviation, t-test and One Way ANOVA. The findings of the study indicate that participant satisfaction, generally was satisfactory. The participant satisfaction towards KPKS arranged in ascending order was physical facilities, followed by course content, lecturers’ presentation and course benefits. The levels of knowledge, skills and confidence of the participants were different and significant after attending the course as compared to before. Knowledge enhancement was most evident in the aspect of curriculum and cocurriculum management whereas, enhancement in skills and confidence was in the aspect of office and financial management. The findings of this study also indicated that there was no difference in the perception of headmasters, senior assistants and the teachers with regards to organizational effectiveness. The headmaster participants were found to be least interested in implementing innovation projects and they were mostly indulged in dayto- day management and administration. A significant and positive but weak relationship was identified between participant satisfaction and learning enhancement. Besides that, a similar weak relationship was also identified between participant satisfaction and organizational effectiveness. However, a weak to moderate relationship was identified between learning enhancement and organizational effectiveness. In whole, majority of the participants welcome the KPKS course and felt satisfied with three main variables namely participant satisfaction, learning enhancement and organizational effectiveness. The implications of these findings suggest that the KPKS course should be continued and retained compulsory for every headmaster who is newly appointed. However, attempts to update the course contents and to cultivate transformational leadership among KPKS participants should be enhanced in order to fulfill the basic needs of Malaysian headmasters.